PENGARUH PERTUMBUHAN PENDUDUK, KESEMPATAN KERJA, DAN INVESTASI TERHADAP TINGKAT PENGANGGURAN DI KOTA PEKANBARU - Dini Agnesia; Hendro Ekwarso; Bunga Chintia Utami (Jurnal Manajemen dan Bisnis, 2023)
This study aims to determine the effect of population growth, Employment opportunities, and investment on the unemployment rate in Pekanbaru City. The data used is time series data for the period 2006-2021. The research uses multiple linear regression analysis method using SPSS version 25 statistical program. The results showed that partially population growth had a negative and significant effect on the unemployment rate, employment opportunities had a negative and  significant effect on the unemployment rate, and invesmant had a negative and significant effect on the unemployment rate in Pekanbaru City. Simultaneously population growth, employment opportunities and investment have a significant effect on the unemployment in Pekanbaru City. The value of Adjusted R-Squared in this study is 0,909, which means that 90,9% of the labor absorption variable can be explained by the independent variables in this study, the remaining 9,1% is explained by other variables outside the research model.